MORAL VALUES AND YOUTH EDUCATION (Scientific journal of the Fergana State University, 2026)
This article discusses the role of moral values in the upbringing of youth. It analyzes the relationship between moral values and the upbringing of youth. Young people can strengthen their moral qualities by learning about their cultural heritage, customs and traditions and integrating them with modern life. The article shows the influence of cultural values on the morality of youth, ways to effectively organize the process of moral upbringing based on moral principles.